2021
DOI: 10.1007/s12560-021-09474-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hepatitis E in 2017 in Bavaria, Germany

Abstract: In the last decade, the number of reported hepatitis E virus (HEV) infections in Germany, including Bavaria, has continued to rise. In order to identify risk factors associated with HEV infection, we investigated notified hepatitis E cases from Bavaria during 2017. The project “Intensified Hepatitis E Surveillance in Bavaria” included interviews with questionnaires, collection and genotyping of stool, serum and food samples. In addition, certain risk factors were examined in a sample comparison with healthy po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
0
5
0
1
Order By: Relevance
“…These changes may be of clinical relevance but studies on the correlation between HEV-3 groups or subtypes and clinical courses yielded conflicting results [ 17–20 ] while infections of rabbits pointed to subtype-specific pathogenicity [ 21 ]. Data for Germany are scarce and either regionally limited or were published more than ten years ago [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These changes may be of clinical relevance but studies on the correlation between HEV-3 groups or subtypes and clinical courses yielded conflicting results [ 17–20 ] while infections of rabbits pointed to subtype-specific pathogenicity [ 21 ]. Data for Germany are scarce and either regionally limited or were published more than ten years ago [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another report also confirmed the presence of infectious virus in pork liver sausage from southern France [ 52 ]. For Germany, several studies have been conducted that identified the consumption of offal and wild boar meat [ 5 ], ready-to-eat pork products [ 53 ] and sausages [ 54 ] as the highest risk factor for hepatitis E disease. Especially liver and liver sausages are main infectious food sources, which is reflected by high viral RNA prevalences ranging from 5.2% in blood [ 17 ], over 18% in liver up to 56.3% in bile samples of wild boars [ 55 ] as well as 13.5% in pig derived liver samples [ 56 ] and 22.0% in liver sausages from Germany [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Auch aus der Schweiz ist ein ähnlicher Erkrankungsfall aufgeklärt worden, der nach dem Verzehr einer anderen Wurstart mit roher Schweineleber aufgetreten war [ 16 ]. Für Deutschland wurden verschiedene Fall-Kontroll-Studien durchgeführt, die auf den Verzehr von Wild und Innereien [ 17 ], Schweineleber, Schweine- und Wildschweinfleisch [ 18 ] sowie Wurstprodukten [ 19 ] als höchsten Risikofaktor für eine Hepatitis-E-Erkrankung hinweisen.…”
Section: üBertragungswege Des Hev-genotypsunclassified